2022
DOI: 10.1002/ppul.25914
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of asthma, allergic rhinitis, and eczema among school‐aged children in Qatar: A Global Asthma Network Study

Abstract: This cross‐sectional study aims to utilize the Global Asthma Network (GAN) questionnaires to estimate the prevalence of asthma, allergic rhinitis, and eczema among children in Qatar. The study population was comprised of children ages 6–7 and 13–14 years, along with their parents or guardians. The English and Arabic versions of the GAN questionnaires were used to collect data for this study. A total of 2646 participants were recruited (1210 in the 6–7 years age group and 1436 in the 13–14 years age group), in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Allergic diseases are a consequence of gene–environment interactions, and not all sensitized individuals develop allergic diseases. Nonetheless, a recent cross-sectional study 84 revealed that the prevalence of diagnosed asthma, lifetime allergic rhinitis, and diagnosed eczema among children in Qatar was as high as 34.6%, 30.9%, and 37.4%, respectively. These findings suggest that a considerable proportion of the sensitized individuals assessed in this present study may also have clinical signs of allergic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Allergic diseases are a consequence of gene–environment interactions, and not all sensitized individuals develop allergic diseases. Nonetheless, a recent cross-sectional study 84 revealed that the prevalence of diagnosed asthma, lifetime allergic rhinitis, and diagnosed eczema among children in Qatar was as high as 34.6%, 30.9%, and 37.4%, respectively. These findings suggest that a considerable proportion of the sensitized individuals assessed in this present study may also have clinical signs of allergic disease.…”
Section: Discussionmentioning
confidence: 99%
“…11 Our study results are consistent with the current Global asthma network study published from the secondary care data from Qatar. 12 According to them when they compare the previous global asthma network study in Qatar back in 2006 showed that noticeable increase in diagnosed eczema (37.4% vs. 22.5%) rates. When comparing these findings to rates from the Gulf region, these rates are higher than those reported for allergic diseases in school children in Saudi Arabia (24%), United Arab Emirates (13%) and in Kuwait (12%).…”
Section: Discussionmentioning
confidence: 99%
“…The authors hypothesized potential causes for this increase, including an increase in urbanization. 6 In a similar study, Yazar and colleagues used the International Study of Asthma and Allergies in Childhood (ISAAC) questionnaires to assess the prevalence of asthma, eczema, and allergic rhinitis in children in Konya, Turkey. The authors found a significant increase in asthma and allergic rhinitis, yet a decrease in eczema, when compared to data from 11 years prior.…”
Section: Updates On Risk Factors For Asthmamentioning
confidence: 99%
“…Allergic rhinitis prevalence remained the same. The authors hypothesized potential causes for this increase, including an increase in urbanization 6 . In a similar study, Yazar and colleagues used the International Study of Asthma and Allergies in Childhood (ISAAC) questionnaires to assess the prevalence of asthma, eczema, and allergic rhinitis in children in Konya, Turkey.…”
Section: Updates On Risk Factors For Asthmamentioning
confidence: 99%